2011
DOI: 10.1210/jc.2011-0651
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Oxidative Stress and Human Leukocyte/Endothelial Cell Interactions in Polycystic Ovary Syndrome Patients with Insulin Resistance

Abstract: This study supports the hypothesis of an association between insulin resistance and an impaired endothelial and mitochondrial oxidative metabolism. The evidence obtained shows that the inflammatory state related to insulin resistance in PCOS induces a leukocyte-endothelium interaction. These findings may explain the increased risk of vascular disease in women with PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 40 publications
4
85
0
5
Order By: Relevance
“…The parallel plate flow chamber in vitro model has been described in detail elsewhere (7). To perform adhesion assays, coverslips containing confluent HUVEC monolayers were inserted into a circular recess in the bottom plate of the flow chamber (maintained at 37°C), to which a 5 · 25 mm portion of the endothelial cells were exposed.…”
Section: Adhesion Assay Levels Of Cytokines and Adhesion Moleculesmentioning
confidence: 99%
“…The parallel plate flow chamber in vitro model has been described in detail elsewhere (7). To perform adhesion assays, coverslips containing confluent HUVEC monolayers were inserted into a circular recess in the bottom plate of the flow chamber (maintained at 37°C), to which a 5 · 25 mm portion of the endothelial cells were exposed.…”
Section: Adhesion Assay Levels Of Cytokines and Adhesion Moleculesmentioning
confidence: 99%
“…3 The mechanism underlying oxidative stress in PCOS is not fully understood, but studies strongly suggest that insulin resistance plays a pivotal role in the pathogenesis of PCOS and encourages oxidative stress. 4 Oxidative stress (OS) is caused by imbalance between pro-oxidant and antioxidants. 5 This ratio can be altered by increased levels of reactive oxygen species (ROS) and /or reactive nitrogen species (RNS), or decrease in antioxidant defence mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in PCOS patients have demonstrated that acute hyperglycemia and IR induce an increase in reactive oxygen species (ROS) production by peripheral blood leukocytes (18,19), activate leukocyte-endothelium interactions (20) and proinflammatory transcription factor nuclear kappa B (NF-kB) (21), and increase levels of proinflammatory cytokines (22). In this way, oxidative stress has been implicated in the etiology of IR in leukocytes from PCOS patients.…”
Section: Introductionmentioning
confidence: 99%